Isolation of Hv-CRKP with co-production of three carbapenemases (blaKPC, blaOXA-181 or OXA-232, and blaNDM-1) and a virulence plasmid: a study from a Chinese tertiary hospital - Li, Ping; Luo, Wan-ying; Xiang, Tian-Xin; Peng, Ting-xiu; Luo, Shuai; He, Zhi-yong; Liao, Wenjian; Wei, Dan-Dan; Liu, Peng; Wan, La-gen; Zhang, Wei; Liu, Yang (Frontiers in Microbiology, 2023)
Background The worldwide dissemination of K. pneumoniae isolates is a significant public health concern, as these organisms possess a unique capacity to acquire genetic elements encoding both resistance and hypervirulence. This study aims to investigate the epidemiological, resistance, and virulence characteristics of K. pneumoniae isolates that carry both virulence plasmids and blaOXA-48-like genes in a tertiary hospital in China. Methods A total of 217 clinical isolates of carbapenem-resistant K. pneumoniae (CRKP) were collected between April 2020 and March 2022. The antimicrobial susceptibility test was conducted to evaluate the drug resistance profile. All isolates were screened for the presence of genes encoding carbapenemases (blaKPC, blaNDM, blaIMP, blaVIM, and blaOXA-48-like), ESBLs genes (blaCTX-M, blaSHV, blaTEM), and virulence plasmid pLVPK-borne genes (rmpA, rmpA2, iucA, iroB, and peg344) using polymerase chain reaction (PCR) amplification. Clonal lineages were assigned using multilocus sequence typing (MLST) and pulsed-field gel electrophoresis (PFGE). The plasmid incompatibility groups were identified using PCR-based replicon typing (PBRT). The transferability of carbapenemase-encoding plasmids and pLVPK-like virulence plasmids was assessed via conjugation. The plasmid location of rmpA2 was determined using S1-Pulsed Field Gel Electrophoresis (S1-PFGE) and southern blotting hybridization. The virulence potential of the isolates was assessed using the string test, capsular serotyping, serum killing assay and a Galleria mellonella larval infection model. Results Of the 217 CRKP clinical isolates collected, 23% were identified as carrying blaOXA-48-like genes. All blaOXA-48-like isolates exhibited resistance to commonly used clinical antimicrobial agents, except for ceftazidime/avibactam, colistin, tigecycline, trimethoprim-sulfamethOXAzole, polymyxin B, and nitrofurantoin. The main common OXA-48-like carbapenemase enzymes were found to be blaOXA-181 and blaOXA-232. MLST and PFGE fingerprinting analysis revealed clonal transmission and plasmid transmission. OXA-48-like producing CRKP isolates mainly clustered in K64 ST11 and K47 ST15. Results of the string Test, serum killing assay (in vitro) and Galleria mellonella infection model (in vivo) indicated hypervirulence. PBRT showed that the blaOXA-181 and blaOXA-232 producing hypervirulent carbapenem-resistant Klebsiella pneumoniae (Hv-CRKP) were mainly carried on ColE-type, IncF, and IncX3. Eight clinical isolates of hv-CRKP were identified as carrying three carbapenem-resistant genes (blaKPC, blaOXA-181 or OXA-232, and blaNDM-1). Moreover, Southern blotting hybridization revealed that all eight isolates had a pLVPK-like virulent plasmid (138.9–216.9 kb) with an uneven number and size of plasmid. Conclusion In our investigation, we have observed the emergence of hv-CRKP carrying blaOXA-48-like genes, which identified two genetic relationships: clonal transmission and plasmid transmission. PBRT analysis showed that these genes were mainly carried on ColE-type, IncF, and IncX3 plasmids. These isolates have been shown to be hypervirulent in vitro and in vivo. Additionally, eight clinical isolates of hv-CRKP were identified as carrying three carbapenem-resistant genes (blaKPC, blaOXA-181 or OXA-232, and blaNDM-1) and carrying a pLVPK-like virulent plasmid. Hence, our findings highlight the need for further investigation and active surveillance of hypervirulent OXA-48-like producing Hv-CRKP isolates to control their transmission.